(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article analyzes the gender characteristics of character speech in literary texts from the perspective of gender linguistics. It examines gender stereotypes reflected in the speech of male and female characters, the linguistic means used to express them, and their communicative and pragmatic functions in literary discourse. In addition, the study explores the linguistic units describing the characters’ appearance, personality, and behavior from a gender perspective and highlights their role in the creation of artistic images.